2019
DOI: 10.1029/2019ja026527
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of IMF Bz Periodic Oscillations on Thermospheric Meridional Winds

Abstract: Previous studies mostly focused on ionosphere and thermosphere responses to strong southward interplanetary magnetic field (IMF) Bz conditions. However, it is not clear how the ionosphere and thermosphere (IT) system responds to Alfvénic quasi‐periodic oscillating IMF Bz conditions. In this article, simulations by the Coupled Magnetosphere Ionosphere Thermosphere model have been used to investigate the effects of IMF Bz temporal variations with 10‐, 30‐, and 60‐min oscillation periods on the coupled IT system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 95 publications
6
35
0
Order By: Relevance
“…In our simulations the maximum PPEF is ~3 mv/m ( Figure not shown), which might be overestimated (Merkin et al, 2005;Wang et al, 2008). As shown in the previous work of Zhang et al (2019), the disturbed wind in the oscillation period of 60 minutes in IMF Bz is strongest when compared to the other two cases with oscillation period of 10 and 30 minutes. Thus, in the present work, we will focus on the 60-min case.…”
Section: Cmit Modelsupporting
confidence: 65%
See 1 more Smart Citation
“…In our simulations the maximum PPEF is ~3 mv/m ( Figure not shown), which might be overestimated (Merkin et al, 2005;Wang et al, 2008). As shown in the previous work of Zhang et al (2019), the disturbed wind in the oscillation period of 60 minutes in IMF Bz is strongest when compared to the other two cases with oscillation period of 10 and 30 minutes. Thus, in the present work, we will focus on the 60-min case.…”
Section: Cmit Modelsupporting
confidence: 65%
“…In the past decades, TADs during magnetic disturbed periods have attracted much attention (e.g., Bruinsma & Forbes, 2007;Liu and Lühr, 2005;Liu et al, 2010Liu et al, , 2014Liu et al, , 2018bOliveira et al, 2017;Otsuka et al, 2004;Shiokawa et al, 2003;Sutton et al, 2009;Thome et al, 1964;Zhang et al, 2019). Previous studies have reported that the storm time energetic particle precipitation and Joule heating (Rodríguez-Zuluaga et al, 2016), the gravity waves (Liu et al, 2014), and the sunset terminator (Beer, 1973) are critical in the generation of TADs.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 shows the geographic longitude and latitude variations of the disturbed electron density, vertical plasma velocity, meridional plasma velocity, and neutral temperature. The enhancements of wind and temperature at -60°~-180° GLon might be related to the longitudinal patterns of electron density, which have a peak at America sector and causing by the topology of geomagnetic eld (Wang and Zhang, 2017;Zhang et al, 2019). The wind and temperature can be affected by electron density via ion-neutral collision.…”
Section: Broken Mean Circulationmentioning
confidence: 99%
“…In the past decades, TADs during magnetic disturbed periods have attracted much attention (e.g., Bruinsma & Forbes, 2007;Liu and Lühr, 2005;Liu et al, 2010Liu et al, , 2014Liu et al, , 2018bOliveira et al, 2017;Otsuka et al, 2004;Shiokawa et al, 2003;Sutton et al, 2009;Thome et al, 1964;Zhang et al, 2019). Previous studies have reported that the storm time energetic particle precipitation and Joule heating (Rodríguez-Zuluaga et al, 2016), the gravity waves (Liu et al, 2014), and the sunset terminator (Beer, 1973) are critical in the generation of TADs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation